Towards a dynamic quality evaluation model for translation - Sharon O'Brien (JoSTrans: The Journal of Specialised Translation)
One of the dominant current methods for translation quality evaluation within the translation industry, i.e. the error typology, is seen as being static and unable to respond to new text types or varying communicative situations and this is leading to rising levels of dissatisfaction. This paper reports on findings from a benchmarking exercise carried out in collaboration with the Translation Automation User Society (TAUS) and eight of its member companies. Eleven translation quality evaluation models were benchmarked. A number of the companies profiled their translatable content according to the parameters of utility, time and sentiment. A review of quality evaluation models in domains related to professional translation leads to a list of alternative quality evaluation methods. The communication channel, the content profile and the parameters of utility, time and sentiment are merged to form building blocks towards a more dynamic quality evaluation model for translation. Examples are given for how such a model could be implemented.